Treatment of concentrates which are formed during nanofiltration purification of water with the high mineralization - Рисухін, Володимир Володимирович; Шаблій, Тетяна Олександрівна; Гомеля, Микола Дмитрович (Eastern-European Journal of Enterprise Technologies, 2011)
The paper presents the results of treatment of sulfate concentrates, which are formed during nanofiltration purification of mine waters and waters with high salinity. It is shown that the effectiveness of the process depends on the flow and the ratio of reagents